2014
DOI: 10.1097/ijg.0b013e31828700de
|View full text |Cite
|
Sign up to set email alerts
|

Glaucoma Awareness in a Hospital Presenting Population in Eastern Nepal

Abstract: Knowledge of glaucoma in this population is very low. No particular groups of people are aware of glaucoma in this part of the country. Health education should be broadly targeted at the population to educate people about the risk factors of glaucoma and thereby prevent needless blindness.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
25
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(31 citation statements)
references
References 20 publications
2
25
4
Order By: Relevance
“…From previous studies, educational status is the significant predictor for awareness of glaucoma. 7,10,14,17,20,21 This finding is also lower than the reports from Ghana (39.3%), 22 Nepal (60.6%), 14 Puducherry, India (45%), 1 Tehran, Iran (46.6%), 23 Birmingham, UK (67%) 24 and Philadelphia, USA (73%). 7 This might be due to differences in socio-demographic and socio-economic status, and participants from developed countries (UK, USA) will access or utilize eye care services easily and will be occupied by health insurance.…”
Section: Discussionmentioning
confidence: 66%
See 1 more Smart Citation
“…From previous studies, educational status is the significant predictor for awareness of glaucoma. 7,10,14,17,20,21 This finding is also lower than the reports from Ghana (39.3%), 22 Nepal (60.6%), 14 Puducherry, India (45%), 1 Tehran, Iran (46.6%), 23 Birmingham, UK (67%) 24 and Philadelphia, USA (73%). 7 This might be due to differences in socio-demographic and socio-economic status, and participants from developed countries (UK, USA) will access or utilize eye care services easily and will be occupied by health insurance.…”
Section: Discussionmentioning
confidence: 66%
“…It can also improve adherence and persistence to treatment and follow-up in patients. 13 Creating public awareness of glaucoma and its risk factors is essential to increase participation in screening programs and possible treatment, 14 thereby reducing its devastating consequences. Contrary to this, lack of awareness appeared to influence self-care practices negatively.…”
Section: Introductionmentioning
confidence: 99%
“…The study in Gondar showed that only 32.7% of adults had no formal education where as in this study more than half (60.2%) of adults had no formal education. From previous studies educational status is the significant predictor for awareness of glaucoma (9,11,14,15,17,22). This finding is also lower than the reports from Ghana (39.3%) (18), Nepal (60.6%) (22), Puducherry, India (45%) (20), Tehran, Iran (46.6%)(23), Birmingham, UK (67%) (24) and Philadelphia, USA (73%) (11).…”
Section: Discussionmentioning
confidence: 75%
“…22,24 Considering lack of awareness on glaucoma in the general population, health education strategies should be targeted at this population to educate people about preventing blindness caused by glaucoma along with other diseases. 25 Refractive error and presbyopia combined accounted for more than two-thirds of all ocular morbidities in the participants examined. This is in line with some of the studies in self-presenters in African nations 26,27 reporting the refractive error (mostly presbyopia) to be the single most important diagnosis in up to 70% of patients.…”
Section: Discussionmentioning
confidence: 99%